Shortening innovation cycles by employee training based on the integration of virtual validation into worker information systems - Fischer, Christian; Lusic, Mario; Bönig, Jochen; Hornfeck, Ruediger; Franke, Jörg (Procedia CIRP, 2015)
Due to rapid developments in technology, the complexity of assembly processes has increased. To meet these challenges, effectively qualified workers are necessary. A worker must have a basic education to understand new training content and be able to translate it into daily work. Also, a fast and efficient data flow from innovations within product development to training is necessary. Especially the use of three-dimensional design data has a great immersion effect for training candidates. The newly learned content is more memorable in comparison to teacher-centered education in schools. We present a solution using a worker information system for this kind of electronic learning. This system may be used even in advance of production. This concept can be extended by providing qualification or even educational content. Using multimedia data derived from computer-aided design and virtual validation, our approach for a novel training concept can be realized.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Assembly; Digital Manufacturing System; Information; Learning